Increased Levels of Markers of Microbial Exposure in Homes with Indoor Storage of Organic Household Waste - Wouters, Inge M. (American Society for Microbiology, 2000)
As part of environmental management policies in Europe, separate collection of organic household waste and nonorganic household waste has become increasingly common. As waste is often stored indoors, this policy might increase microbial exposure in the home environment. In this study we evaluated the association between indoor storage of organic waste and levels of microbial agents in house dust. The levels of bacterial endotoxins, mold β(1→3)-glucans, and fungal extracullar polysaccharides (EPS) of Aspergillus and Penicillium species were determined in house dust extracts as markers of microbial exposure. House dust samples were collected in 99 homes in The Netherlands selected on the basis of whether separated organic waste was present in the house. In homes in which separated organic waste was stored indoors for 1 week or more the levels of endotoxin, EPS, and glucan were 3.2-, 7.6-, and 4.6-fold higher, respectively (all P < 0.05), on both living room and kitchen floors than the levels in homes in which only nonorganic residual waste was stored indoors. Increased levels of endotoxin and EPS were observed, 2.6- and 2.1-fold (P < 0.1), respectively, when separated organic waste was stored indoors for 1 week or less, whereas storage of nonseparated waste indoors had no effect on microbial agent levels (P > 0.2). The presence of textile floor covering was another major determinant of microbial levels (P < 0.05). Our results indicate that increased microbial contaminant levels in homes are associated with indoor storage of separated organic waste. These increased levels might increase the risk of bioaerosol-related respiratory symptoms in susceptible people.